Cell number counts – The fw2.2 and CNR genes and implications for controlling plant fruit and organ size - Guo, Mei; Simmons, Carl R (Plant science (Limerick), 2011)
Two key determinants of plant and organ size are cell number and cell size, and altering either one may affect the plant organ size, but cell number control often plays a predominant role in natural populations. Domesticated crops usually have larger fruit and harvested organ sizes than wild progenitors. Crop yields have increased significantly by breeding, often via heterosis, which is associated with increased plant and organ size primarily achieved by cell number increases. A small class of genes is now known that control plant and organ sizes though cell number or cell size. The fw2.2 gene was found to control a major QTL for tomato fruit size by negatively affecting cell numbers. Orthologs to these fw2.2 genes underlie QTLs for fruit sizes in other species, and their expression can be negatively correlated with increased cell number. In maize decreased or increased expression of the fw2.2 ortholog ZmCNR1, increases or decreases cell number, respectively, thereby affecting maize organ size throughout the plant and thus also whole plant size. Therefore, these genes should now be considered as more general regulators of plant cell number and organ size. The exact molecular function of these transmembrane domain proteins remains unknown, as does any clear relationship to the cell cycle. Because these genes control organ sizes in diverse plants and important crop species, and because they can affect whole plant size, interest arose into how effects of such genes could parallel agronomic crop improvements, in particular that by heterosis, as it also affects cell number. In joining these subjects here in discussion we speculate on how single gene cell number regulation and heterosis may cooperate in crop improvement.